Digital Revolution in Land Affairs: Transformation of Land Certificates Through Electronic Mortgage Service - Clarabella Marella; Ana Silviana (Universitas Negeri Semarang, 2024)
This study analyzes the digital transformation of Indonesia’s land administration through the implementation of the Electronic Mortgage (HT-el) system, which replaces conventional mortgage registration with a fully online process. Using a normative legal research method supported by deductive qualitative analysis, this research examines the regulatory, technical, and institutional challenges faced by Land Deed Officials (PPAT) in adapting to the digital environment. Findings reveal that the transition to electronic land certificates encounters multiple obstacles, including insufficient infrastructure, inconsistent data integration, limited digital literacy, and ambiguities in legal accountability between PPAT and other stakeholders. Despite these challenges, the HT-el system enhances transparency, reduces document falsification risks, and accelerates service delivery. However, its long-term success depends on strengthening legal frameworks, improving human resource capacity, ensuring cybersecurity, and fostering public digital inclusion. This study contributes to the discourse on e-governance and legal modernization by highlighting how technological adaptation reshapes legal certainty and administrative justice within Indonesia’s agrarian reform.